2002
DOI: 10.1074/jbc.m203343200
|View full text |Cite
|
Sign up to set email alerts
|

LAT Displacement from Lipid Rafts as a Molecular Mechanism for the Inhibition of T Cell Signaling by Polyunsaturated Fatty Acids

Abstract: Polyunsaturated fatty acids (PUFAs) suppress immune responses and inhibit T cell activation through largely unknown mechanisms. The displacement of signaling proteins from membrane lipid rafts has recently been suggested as underlying PUFA-mediated T cell inhibition. We show here that PUFA treatment specifically interferes with T cell signal transduction by blocking tyrosine phosphorylation of LAT (linker for activation of T cells) and phospholipase C␥1. A significant fraction of LAT was displaced from rafts b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
2
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(113 citation statements)
references
References 49 publications
5
105
2
1
Order By: Relevance
“…However, a large variety of eicosanoids with the potential to influence DC function remains that has to be analyzed in detail before a possible implication of eicosanoids in mediating PUFA effects on DCs can definitely be ruled out. Lipid raft modification has been shown to underlie inhibitory effects of PUFAs on T cell signaling (21,30). PUFAs were incorporated into DC membrane lipids in our studies and probably also in raft lipids since raft lipid alterations by exogenous fatty acids generally reflect those in cellular membranes (21).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, a large variety of eicosanoids with the potential to influence DC function remains that has to be analyzed in detail before a possible implication of eicosanoids in mediating PUFA effects on DCs can definitely be ruled out. Lipid raft modification has been shown to underlie inhibitory effects of PUFAs on T cell signaling (21,30). PUFAs were incorporated into DC membrane lipids in our studies and probably also in raft lipids since raft lipid alterations by exogenous fatty acids generally reflect those in cellular membranes (21).…”
Section: Discussionmentioning
confidence: 91%
“…showed that PUFA treatment alters T cell membrane lipid composition in vitro and in vivo (21,27,28) causing functional defects in T cell signaling (29,30). Hence, we investigated whether also DCs incorporate exogenous PUFAs into cell membranes leading to altered membrane lipid composition.…”
Section: Pufa Treatment Leads To Altered Membrane Lipid Composition Omentioning
confidence: 99%
“…concentrations of these fatty acids, compete for cyclooxygenase with arachidonic acid, 64 affect membrane raft function in signal transduction 65 and modulate the activity of transcription factors such as PPARs, liver  receptors or sterol regulatory element-binding protein-1c. 63 Alteration of eicosanoid synthesis, activation of PPAR-g and inhibition of liver  receptors are attractive candidates for n-3 PUFA action in adipose tissue of obese animals.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, splenic CD3 ϩ T cells isolated from mice fed diets enriched with either fish oil or corn oil were stimulated via the TCR/CD3 complex to investigate changes in microdomain localization. PKC, LAT, and Fas/CD95 were selected, because T cell activation and apoptosis require their translocation to rafts (27,35,58). PKC, LAT, and Fas/CD95 were homogeneously distributed at the plasma membrane in unstimulated cells; however, they became concentrated in distinct patches in a large proportion of stimulated cells.…”
Section: Dietary N-3 Pufa Partially Displace Pkc From Membrane Raftsmentioning
confidence: 99%